2022
DOI: 10.1108/jgm-02-2022-0006
|View full text |Cite
|
Sign up to set email alerts
|

African immigrants self-employment journey: navigating contextual challenges in South Africa

Abstract: PurposeThe study explores experiences of African immigrants in their self-employment journey. South Africa has been receiving many African immigrants seeking for socio-economic survival. This presents a gap to understand the self-employment journey of such immigrants post-settlement.Design/methodology/approachA qualitative inquiry is used with semi-structured interviews using a sample of African immigrants based in South Africa. Narrative enquiry was utilised in trying to understand the African immigrant self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 57 publications
2
4
1
Order By: Relevance
“…[ 36 ] indicates that the complexities of itinerant traders relate more to a lack of business skills, crime, conflict with native traders, police harassment and storage problems. The findings of this study also controvert what [ 14 ] observed among African immigrant entrepreneurs in South Africa, where they encountered bottlenecks connected with institutional factors. This is because, although some of these challenges came up in the study, they did not feature as strong obstacles or risks in the immigrants’ business operations.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…[ 36 ] indicates that the complexities of itinerant traders relate more to a lack of business skills, crime, conflict with native traders, police harassment and storage problems. The findings of this study also controvert what [ 14 ] observed among African immigrant entrepreneurs in South Africa, where they encountered bottlenecks connected with institutional factors. This is because, although some of these challenges came up in the study, they did not feature as strong obstacles or risks in the immigrants’ business operations.…”
Section: Discussioncontrasting
confidence: 99%
“…Participants unanimously indicated that they had difficulty renting accommodation due to high rental charges in the city, which, in their view, led to overcrowded dwellings. These findings are said to be in tandem with what [ 14 ], and the [ 21 ] described in their study: that most immigrants, upon arrival at their destination, meet serious problems in accessing decent housing and are generally compelled to live in squalor conditions. The present findings relating to the immigrants' accommodation challenges could have dire health repercussions, including outbreaks of diseases such as Cerebrospinal Meningitis and tuberculosis.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations